Enhanced tuning efficiency and sensitivity based on mode transition of symmetric cladding modes in fibre Bragg grating overlaid with high refractive nm-thick film. Issue 12 (12th July 2021) - Wu, Yue; Zhang, Yingcong; Luo, Haimei; Wang, Changjing; Zhu, Yuanfeng; Wang, Yifan; Yuan, Wen; Tan, Hai; Wang, Xianping
Abstract : In this paper, we theoretically investigate the tuning characteristics of a four-layer structure optic fibre Bragg grating (FBG) coated with high refractive index (HRI) overlay. The attention is mainly focused on the analysis of the effects of the mode transition and the mode reorganization on the tuning sensitivity to the overlay HRI of the structure. The cladding diameter of FBG is also considered as a parameter for enhancing the sensitivity of FBG to HRI. Moreover, different cladding modes show different sensitivities. For FBG with negative thermo-optical coefficient coating material, the thermal property of the structure could be effectively suppressed by selecting an optimal fibre cladding diameter. The reported results demonstrate the possibility of this structure can be used as thermal-stable tunable all-fibre photonic device, such as filter, modulator and sensing element.